Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Literasi Sains pada Materi Ekosistem - Fadlila, Shafira Nur; Paujiah, Epa; Solikha, Maratus; Hadiansah, Hadiansah; Cahyanto, Tri (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to develop a Student Worksheet (LKPD) based on scientific literacy on the topic of ecosystems, assess its feasibility, and gather teacher feedback on the developed LKPD. The research employed a Research and Development (R&D) which includes three stages: Analyze, Design, and Develop. Data collection techniques involved a preliminary study through interviews to obtain initial information. The developed LKPD was then validated through expert validation questionnaires, readability tests by teachers and students, and student response questionnaires. The subject of this research was the scientific literacy-based LKPD, with participants consisting of one biology teacher and 15 tenth-grade students from MAN 1 Kota Bandung. The feasibility of the LKPD was assessed by two experts: a subject matter expert and a media expert. Data analysis was conducted using a Likert scale based on predetermined assessment criteria. The results showed that the material feasibility scored 85.33% with a "very valid" category. Media feasibility scored 91.25%, also in the "very valid" category. The biology teacherâ€™s readability test scored 81.33%, classified as "very valid", while the studentsâ€™ readability test scored 90.06%, indicating the highest category of "easy to understand". The student response test scored 91.46% in the "very positive" category. Based on these results, the scientific literacy-based LKPD on ecosystem material is considered highly valid/feasible and can be used as a teaching material to support biology learning, particularly in enhancing students’ scientific literacy in the ecosystem topic.